Morphometric Analysis of the Orbital Process of the Palatine Bone and its Relationship to Endoscopic Orbital Apex Surgery - Mueller, Sarina K.; Freitag, Suzanne K.; Bleier, Benjamin S. (Ophthalmic Plastic and Reconstructive Surgery, 2018)
BACKGROUND: Endoscopic approaches to the orbit improve the ability to directly access apical lesions while minimizing manipulation of normal structures. Inferomedial orbital access is limited by the orbital process of the palatine bone (OPPB) which prevents dissection and retraction in the inferolateral vector. OBJECTIVE: The objective of this study was to examine the morphometric characteristics of the OPPB and quantify the benefit of complete resection to surgical access. METHODS: Morphometric osteologic measurements of the OPPB were performed in 59 human skulls. A radius subtended by the OPPB was calculated to generate a hemispheric dissection corridor achievable by complete resection of the OPPB. Cadaveric and live surgical dissections were then performed on 15 orbits to develop discreet endoscopic surgical landmarks which could be used to both identify the OPPB and verify complete resection. RESULTS: The mean(± SD) radius of the OPPB was 0.47 ± 0.28 cm. Complete OPPB resection provided an additional 0.36 ± 0.42 cm of surgical exposure within the inferomedial apex. Relative to the Caucasian (n = 27) skulls, the radii in the Asian (n = 27) and African (n = 5) skulls were significantly smaller (p < 0.001 and p = 0.02, respectively). CONCLUSION: The OPPB significantly limits surgical access to the inferomedial orbital apex during endoscopic approaches. Complete surgical resection of the OPPB improves surgical exposure facilitating retraction of the inferior rectus muscle and circumferential dissection of lesions within this space. Knowledge of the morphology and clinical relevance of this structure provides an opportunity to improve surgical exposure for relevant pathologic assessment and optimize endoscopic surgical outcomes.
EVALuna2:210635